2021
DOI: 10.3390/ijerph18073505
|View full text |Cite
|
Sign up to set email alerts
|

Does Paradoxical Leadership Facilitate Leaders’ Task Performance? A Perspective of Self-Regulation Theory

Abstract: As an emerging Chinese indigenous leadership style, paradoxical leadership has received considerable attention from researchers. Many studies have demonstrated the positive impact of paradoxical leadership on employees, teams, and organizations; however, there is less information on how paradoxical leaders influence their own work outcomes. On the basis of self-regulation theory, in this study, we examined the impact of paradoxical leadership on leaders’ task performance. In addition, we investigated the media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 73 publications
0
12
0
Order By: Relevance
“…The study contributes to the research in several ways. First, as stated, there is abundant research that has looked at the positive side of paradoxical leadership (Chen et al , 2021; Li et al , 2018; Sparr et al , 2022; Zhang et al , 2021; Zhang and Han, 2019; Zheng et al , 2018). Similarly, some recent research also looks at the drawbacks of the paradoxical leadership on the leader (Bashir, 2021; Julmi, 2021; Shao et al , 2019) as well as the followers (Ishaq et al , 2021; She et al , 2020; Yang et al , 2021; Zhang et al , 2022).…”
Section: Discussion Implications and Future Researchmentioning
confidence: 99%
“…The study contributes to the research in several ways. First, as stated, there is abundant research that has looked at the positive side of paradoxical leadership (Chen et al , 2021; Li et al , 2018; Sparr et al , 2022; Zhang et al , 2021; Zhang and Han, 2019; Zheng et al , 2018). Similarly, some recent research also looks at the drawbacks of the paradoxical leadership on the leader (Bashir, 2021; Julmi, 2021; Shao et al , 2019) as well as the followers (Ishaq et al , 2021; She et al , 2020; Yang et al , 2021; Zhang et al , 2022).…”
Section: Discussion Implications and Future Researchmentioning
confidence: 99%
“…As shown in Appendices 1 and 2, the coefficients of R 2 and △R 2 values are all statistically significant, and then it reveals evidence of sensitivity (see Appendix 1 and 2) (Christopher Frey and Patil, 2002). Following previous research studies, all items across five dimensions form an overall measurement and provide a comprehensive view of paradoxical leadership for subsequent analyses (Zhang et al , 2015; Li et al , 2018; She et al , 2020; Xue et al , 2020; Chen et al , 2021). Thus, all dimensions of sources regarding nurses’ perceptions of paradoxical leadership in the workplace were noted.…”
Section: Methodology and Measurementmentioning
confidence: 99%
“…Since leaders face contradictory and competing demands (Clegg et al, 2002), PLB is argued to be beneficial for organizations and employes. Leaders engaging in paradoxical behaviors can fulfill conflicting organizational needs and address the followers’ individual needs at the same time (Chen et al, 2021; Zhang et al, 2015). As beneficiaries of leader paradoxical behaviors, it has been shown that followers are motivated to work more proficiently and proactively (Fürstenberg et al, 2021; Zhang et al, 2015), give more voice (Li et al, 2020), and demonstrate more ambidextrous behaviors (i.e., both exploration and exploitation) at work (Kauppila & Tempelaar, 2016; Klonek et al, 2021).…”
Section: Paradoxical Leader Behaviors and Follower Performancementioning
confidence: 99%
“…Second, when developing PLB theory, Zhang et al (2015) cautioned about the potential boundaries of the functioning of PLB. Empirical investigations to date have mainly focused on follower characteristics as boundary conditions (for an exception, see Chen et al, 2021). For example, Ishaq et al (2021) found that followers' psychological capital reinforced the positive relationship between PLB and follower performance.…”
Section: Introductionmentioning
confidence: 99%